2017
DOI: 10.1016/bs.mie.2016.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Deep Profiling of Proteome and Phosphoproteome by Isobaric Labeling, Extensive Liquid Chromatography, and Mass Spectrometry

Abstract: Mass spectrometry-based proteomics has experienced an unprecedented advance in comprehensive analysis of proteins and posttranslational modifications, with particular technical progress in liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS) and isobaric labeling multiplexing capacity. Here we introduce a deep proteomics profiling protocol that combines 10-plex tandem mass tag (TMT) labeling with an optimized LC-MS/MS platform to quantitate whole proteome and phosphoproteome. The major steps in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
112
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 43 publications
0
112
0
Order By: Relevance
“…Furthermore, this decrease was specific to MAGE-A3/6, as several control proteins showed minimal change under similar conditions ( Fig 1B). To fully understand the selectivity of MAGE-A3/6 regulation under these conditions and validate our findings in another cell line, we performed quantitative proteomic analysis of A375 melanoma cells with or without nutrient deprivation, using multiplex tandem mass tag (TMT) labeling, combined with two dimensional liquid chromatography for extensive peptide fractionation, and tandem mass spectrometry for peptide/protein identification and quantification (TMT-LC/LC-MS/MS) [33]. We were able to quantitate the relative abundance of 8,649 proteins (false discovery rate < 1%) and found that only a small number significantly change.…”
Section: Rapid and Selective Degradation Of Mage-a3/6 Upon Cellular Smentioning
confidence: 92%
“…Furthermore, this decrease was specific to MAGE-A3/6, as several control proteins showed minimal change under similar conditions ( Fig 1B). To fully understand the selectivity of MAGE-A3/6 regulation under these conditions and validate our findings in another cell line, we performed quantitative proteomic analysis of A375 melanoma cells with or without nutrient deprivation, using multiplex tandem mass tag (TMT) labeling, combined with two dimensional liquid chromatography for extensive peptide fractionation, and tandem mass spectrometry for peptide/protein identification and quantification (TMT-LC/LC-MS/MS) [33]. We were able to quantitate the relative abundance of 8,649 proteins (false discovery rate < 1%) and found that only a small number significantly change.…”
Section: Rapid and Selective Degradation Of Mage-a3/6 Upon Cellular Smentioning
confidence: 92%
“…Protein concentration was measured by the BCA method (Thermo Scientific) and confirmed by Coomassie-stained short SDS gel 27 . After digestion, the peptides were desalted, resuspended in HEPES buffer (50 mM, pH 8.5) and labeled by individual 10-plex MT reagents (Thermo Scientific, E.coli peptides by 10 channels, rat peptides by 8 channels from 126 to 130N) following manufacturer's instruction 28,29 . Finally, these peptides were then mixed as specified (Figure 1), desalted again and dried.…”
Section: Methodsmentioning
confidence: 99%
“…With the technical advances of mass spectrometry, the peptidomics have increased application, and success in investigating endogenously produced protein fragments (Bai et al, ; O'Brien & Timms, ). Using peptidomics, a group of endogenous peptides can be identified, which can broaden our knowledge of many biological processes (Cui et al, ; Gemperline et al, ; Tsuchiya, Iwakura, Minamino, Kangawa, & Sasaki, ).…”
Section: Introductionmentioning
confidence: 99%